2020
DOI: 10.1007/978-3-030-44429-7_8
|View full text |Cite
|
Sign up to set email alerts
|

On Understanding How Developers Perceive and Interpret Privacy Requirements Research Preview

Abstract: Context and motivation]Ensuring privacy of users' data has become a top concern in software development, either to satisfy users' needs or to comply with privacy laws. The problem may increase by the time a new law is in the vacancy period, and companies are working to understand how to comply with it. In addition, research has shown that many developers do not have sufficient knowledge about how to develop privacy-sensitive software. [Question/problem] Motivated by this scenario, this research investigates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 8 publications
1
19
0
7
Order By: Relevance
“…The tool developed by the authors provides a method to enforce privacy and security requirements. Peixoto et al [51] investigated the personal factors that affect the understanding of the privacy requirements by software developers. The authors conducted thirteen interviews at six private companies and found nine personal factors that affect how software developers perceive and interpret privacy requirements.…”
Section: Rq1 According To the Literature What Are The Methodologiementioning
confidence: 99%
“…The tool developed by the authors provides a method to enforce privacy and security requirements. Peixoto et al [51] investigated the personal factors that affect the understanding of the privacy requirements by software developers. The authors conducted thirteen interviews at six private companies and found nine personal factors that affect how software developers perceive and interpret privacy requirements.…”
Section: Rq1 According To the Literature What Are The Methodologiementioning
confidence: 99%
“…More than 10 years earlier, the FTC showed that enacting COPPA had an effect on encouraging websites to be transparent and more protective of their users' data [24]. These reports spurred further research that aimed to understand the privacy behaviors of mobile apps at a larger scale [43,47,54,57,[62][63][64]76], examine consumer expectations of privacy [48,56,58,66,71,75], and understand app developers' privacy practices [53,61,65,67].…”
Section: Related Workmentioning
confidence: 99%
“…Other studies investigated public forums to see how developers deal with privacy regulations and changes to them, finding that they mostly try to uphold standards defined by large companies [62] or are focused on recent changes or events [36] when discussing privacy. When asked to solve privacy-focused tasks, developers tend to use betterdocumented alternatives and copy examples, which could be adopted by privacy-friendly services [28], and that they often struggle with embedding privacy into their application due to lack of knowledge, privacy contradicting app requirements, or task complexity [50,57].…”
Section: Website Protectionmentioning
confidence: 99%
“…We cannot verify to what degree participants were actually involved with the provided website or if they consistently answered for the same site. Analyzing self-reported information is common in research involving developers [1,42,50,57] and manual inspection of survey responses suggests that participants answered consistently. Our survey was voluntary and uncompensated, which might have introduced bias, especially since experts tend to be well-paid and hard to reach.…”
Section: Limitationsmentioning
confidence: 99%